sRNA(154) a newly identified regulator of nitrogen fixation in Methanosarcina mazei strain Gö1 - Prasse, Daniela (RNA Biol, 2017)
Trans-encoded sRNA(154) is exclusively expressed under nitrogen (N)-deficiency in Methanosarcina mazei strain Gö1. The sRNA(154) deletion strain showed a significant decrease in growth under N-limitation, pointing toward a regulatory role of sRNA(154) in N-metabolism. Aiming to elucidate its regulatory function we characterized sRNA(154) by means of biochemical and genetic approaches. 24 homologs of sRNA(154) were identified in recently reported draft genomes of Methanosarcina strains, demonstrating high conservation in sequence and predicted secondary structure with two highly conserved single stranded loops. Transcriptome studies of sRNA(154) deletion mutants by an RNA-seq approach uncovered nifH- and nrpA-mRNA, encoding the α–subunit of nitrogenase and the transcriptional activator of the nitrogen fixation (nif)-operon, as potential targets besides other components of the N-metabolism. Furthermore, results obtained from stability, complementation and western blot analysis, as well as in silico target predictions combined with electrophoretic mobility shift-assays(,) argue for a stabilizing effect of sRNA(154) on the polycistronic nif-mRNA and nrpA-mRNA by binding with both loops. Further identified N-related targets were studied, which demonstrates that translation initiation of glnA(2)-mRNA, encoding glutamine synthetase2, appears to be affected by sRNA(154) masking the ribosome binding site, whereas glnA(1)-mRNA appears to be stabilized by sRNA(154). Overall, we propose that sRNA(154) has a crucial regulatory role in N-metabolism in M. mazei by stabilizing the polycistronic mRNA encoding nitrogenase and glnA(1)-mRNA, as well as allowing a feed forward regulation of nif-gene expression by stabilizing nrpA-mRNA. Consequently, sRNA(154) represents the first archaeal sRNA, for which a positive posttranscriptional regulation is demonstrated as well as inhibition of translation initiation.